Conformational Changes of the Alanine Dipeptide in Water-Ethanol Binary Mixtures - Almeida, Glauco G. [UNESP]; Cordeiro, Joao M. M. [UNESP]; Elena Martin, M.; Aguilar, Manuel A. (Amer Chemical Soc, 2016)
Experimental work developed in the last years has evidenced the capacity of alcohols and polyalcohols to modify the energy landscape of peptides and proteins. However, the mechanism underlying this effect is not clear. Taking as a model system the alanine dipeptide (AD) we perform a QM/MM study in water, ethanol, and a 40-60% in volume water- ethanol mixture. The AD molecule was described at the MP2/aug-cc-pVDZ level. In polar solution, only alpha(R) and PPII conformers contribute in an appreciable way to the conformational equilibrium. The final in solution alpha(R)-PPII free energy difference is determined from the interplay between the internal energy of the dipeptide and the solute-solvent interaction free energy. Internal energy favors the formation of PPII, whereas, on the contrary, solute-solvent interaction is favorable to alpha(R), so any factor that decreases the solute-solvent interaction free energy will increase the PPII population. The addition of ethanol increases the stability of the PPII conformer. Our results point to the presence of preferential solvation in this system, the composition of the first solvation shell in the binary mixture being dominated by water molecules. Remarkably, this fact does not affect the differential conformational stability that is controlled by long-range interactions. From the analysis of solvent density maps it is concluded that, in the water-ethanol mixture, ethanol molecules are more likely found around the alanine side chain and the carbonyl group, but while in PPII ethanol molecules interact mainly with the carbonyl group of the N-terminal end, in CS the interaction is with the carbonyl group of the C-terminal end. In alpha(R), ethanol interacts with both carbonyl groups.